Transfer Pricing Terhadap Penerimaan Negara Pada Sektor Pajak di Indonesia - Aprilia Tri Santi (University of Jember, 2016)
The development of the current globalization has made large companies throughout the world to plant their branch companies out of their country. Their companies are called Multinational Companies. The negative impact caused by this development is that with the presence of branches in various countries, a company in a country can move some or all of the profits they earn to other countries that are still in the same parent company. Transfer of profits is done from countries that have high tax rates to countries that have low tax rates between companies that have special relationships. This is done so that the income tax is reduced. This event can be called transfer pricing or transfer pricing between parties that have special relationships. This article examines how the process of transfer pricing and legal consequences arises from tax avoidance events through transfer pricing. Transfer pricing greatly affects the amount of state income, especially in the income tax sector because the tax burden paid by companies is not following the profits they earn. State losses resulting from transfer pricing events reach 1300 trillion annually. But the weakness of institutions in the Tax Directorate General makes transfer pricing events grow. This article concludes with a suggestion that the government further increase tax control by the subject of Permanent Business Forms tax so that taxpayers become law-abiding. KEYWORDS: Transfer Pricing, Tax Avoidance Practices, Income Tax.